Pengaruh Ukuran Perusahaan, Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan (Sub Sektor Makanan dan Minuman di BEI 2020-2022) - Saniah, Siti; Sundarta, Imam; Hurriyaturrohman, Hurriyaturrohman (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to investigate how company size, capital structure, and profitability impact the value of companies in the beverage and food sub-sector listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling method employed was purposive sampling, which selects samples based on specific criteria relevant to the variables under study. Out of a population of 70 companies meeting the criteria, 21 companies were selected, resulting in a total of 63 observations for the study. Secondary data from financial reports available on the Indonesia Stock Exchange official website was used, collected through the documentation method. Multiple linear regression analysis was used for data analysis. The findings show that company size has a statistically insignificant negative effect, while capital structure and profitability have a statistically significant positive effect on company value. When analyzed together, company size, capital structure, and profitability collectively influence company value.